The Role of the Financial Services Authority as a Strategic Partner for the Progress of the Indonesian Capital Market - Lubis, Putri Kemala Dewi; Sitio, Fridayani M.; Tampubolon, Novia Christiani; Sinaga, Dewi Larasati; Hasibuan , Mhd Rifqi Farhan (Indonesian Journal of Banking and Financial Technology, 2024)
The Indonesian capital market still faces several obstacles, including relatively low growth rates, limited access to finance, and significant financial risks. Financial services authorities can become strategic partners that encourage capital market growth and stability by innovating products and services, increasing financial access, and collaborating with other parties. This research uses a descriptive type of research with a literature review and reading sources related to the research collected using the literature review research method. This research aims to explore the role of financial services authorities as strategic partners in supporting the progress of the capital market in Indonesia. Based on various sources and theories, it can be concluded that as a supervisory authority, the OJK regulates and supervises institutional, prudential and sound aspects and carries out inspections of financial institutions to ensure that each financial institution is healthy and able to serve the public interest. OJK regulations apply to the issuance of operating permits for stock exchanges, clearing and guarantee institutions, investment fund custodians and settlement agents, securities companies, investment advisors, securities bureaus and other legal entities. OJK also collaborates with various related parties, including educational institutions, the financial industry and the government, to encourage innovation in the Indonesian capital market. The impact of this OJK partnership can help mitigate community losses due to errors by capital market players.